Antioxidant activity of co-products from milk fat processing and their enzymatic hydrolysates obtained with different proteolytic preparations. (September 2016) - Ripollés, Daniel; Parrón, José Antonio; Calvo, Miguel; Pérez, María Dolores; FitzGerald, Richard J.; Sánchez, Lourdes
Abstract: Different co-products are generated from bovine milk during the manufacture of butter or anhydrous milk fat. Those co-products have a similar composition to milk, though they are enriched in fat and components from the milk fat globule membrane. The antioxidant activity of some commercial products (skim milk, butter serum and buttermilk) and raw buttermilk was assayed using the 2, 2-diphenyl-1-picrylhydrazyl radical scavenging assay. Commercial co-products showed higher antioxidant activity than raw buttermilk when tested at >10 mg mL −1 . These products were incubated with Alcalase, Prolyve and Corolase PP to determine the effect of enzymatic hydrolysis on their antioxidant activity; hydrolysates obtained were characterised by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and reverse-phase high performance liquid chromatography. Hydrolysis with Corolase PP produced the hydrolysates with the highest antioxidant activity. Products derived from milk fat processing and their hydrolysates may therefore be considered as a natural source of antioxidant compounds for application as value-added ingredients.